Decentralizacja wydatków publicznych w wybranych krajach Unii Europejskiej - Kasperowicz-Stępień, Alicja (Decentralization of Public Expenditures in Selected Countries of the European Union, 2009)
The meaning of the decentralization is not clearly defined in literature. The experience of Poland and other European Union (EU) countries shows that decentralization is closely related with to the development of local government. This paper discusses the decentralization problem and shows that the main indicator to measure the level of decentralization is a relation between public expenditures and GDP. The article presents the role of local government of the new EU countries in public expenditures
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 2, s. 97-101